If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4f(x) = 2(4f)(x) + 1 Multiply f * x 4fx = 2(4f)(x) + 1 Remove parenthesis around (4f) 4fx = 2 * 4f(x) + 1 Multiply 2 * 4 4fx = 8f * x + 1 Multiply f * x 4fx = 8fx + 1 Reorder the terms: 4fx = 1 + 8fx Solving 4fx = 1 + 8fx Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-8fx' to each side of the equation. 4fx + -8fx = 1 + 8fx + -8fx Combine like terms: 4fx + -8fx = -4fx -4fx = 1 + 8fx + -8fx Combine like terms: 8fx + -8fx = 0 -4fx = 1 + 0 -4fx = 1 Divide each side by '-4x'. f = -0.25x-1 Simplifying f = -0.25x-1
| 16+8x=47-3x | | 2x^2+21x-5.7=0 | | 2(x-20)=15 | | 13-7x+3x=-6-5x+3 | | 13x+2y=407 | | 9a-5*a=7 | | 132=c-(249) | | 132=(-249) | | 11x=3600+6x | | 2x+10y=34 | | (x)(x)-11x-80=0 | | 3x+7=x+41 | | 24x+10x+1=0 | | Lnx(Lnx-4)=0 | | X-.35x=50000 | | 4p^2-8p+578=0 | | 3x+5+7x-10=90 | | x^3-1.413*x^2+0.013=0 | | 2(5y+6)=82 | | log[7](4)-log[7](3x)= | | 0=4b^2-76b+16 | | 4x+6=5-3x | | 0=4b^2-200b+16 | | x^2+5mx+16=0 | | 0=4b^2-96b+16 | | x+7/6-x/3=-2 | | 0=12t^2-42t+30 | | 3x-2+2y+1+x-w+1+3-4w=22 | | 4t+7=9t-13 | | 25x^2-160x+220=0 | | 0=b^2-24b+4 | | 2/x+1/x-1=2 |